Analisis Efektivitas Dan Kontribusi Penerimaan Pajak Reklame Terhadap Pendapatan Asli Daerah Kabupaten Pekalongan - Rizka Ariyanti; Singgih Setiawan; Nur Cahyati (BALANCE: Economic, Business, Management and Accounting Journal, 2020)
The purpose of this study was to determine the effectiveness and contribution of advertisement tax revenue to local revenue in Pekalongan Regency in 2014-2018. This study uses secondary data obtained from the Regional Financial Management Agency of Pekalongan Regency.The research method used is descriptive method and data collection techniques. Observations were made using observation, interview, documentation and literature study techniques. The method in this study uses qualitative and descriptive research types.The results of this study indicate that the effectiveness of advertisement tax revenue during the period 2014 - 2018 has a ratio of more than 100% so it can be said to be very effective. The contribution of advertisement tax to Pekalongan Regency's Regional Revenue (PAD) during the period 2014 - 2018 with the contribution ratio is still below 10% so it is said to be very less. Keywords       : Effectiveness, Contribution, Original Regional Revenue